COMPARISON OF PRE AND POST-TURP EVALUATION IN BPH PATIENTS USING IPSS AND UROFLOWMETRY IN TERTIARY HOSPITAL - Putra, Fikri Alam Riza; Daryanto, Besut; Kustono, Andri (Indonesian Journal of Urology, 2024)
Objective: To present the data about LUTS using International Prostatic Symptoms Score (IPSS) and uroflowmetry on BPH patients following TURP. Material & Methods: This retrospective study reviewed patients diagnosed as BPH with LUTS undergone TURP from Dr. Saiful Anwar General Hospital medical records from January 2021 to January 2023. The basic clinical characteristics, IPSS, and uroflowmetry results were collected. Furthermore, the comparison of IPSS score and uroflowmetry prior and 7 days after surgery were analyzed. Results: From a total of 286 patients, 94 patients met the inclusion criteria. Improvement of LUTS and quality of life (QoL) obtained from IPSS were observed before and after TURP (19.13 vs 2.78, p<0.001; 4.38 vs 0.33, p<0.001). Similar improvement was also showed for maximum flow rate (QMax) and post-void residual (PVR) volume obtained from uroflowmetry result (7.90 vs 17.85, p<0.001; 66.25 vs 27.05, p<0.001) with 90.43% patients had Qmax >15 ml/sec after the procedure. Conclusion: This study showed the evidence of early improvement of IPSS and uroflowmetry results in BPH patients after TURP. The indicators were sufficient to evaluate the satisfaction result of patient complaining LUTS. Keywords: BPH, IPSS, uroflowmetry, TURP.